Hipertrofia ventricular esquerda em pacientes com doença renal crônica em hemodiálise: análise comparativa entre eletrocardiograma, radiografia de tórax e ecocardiograma - Costa, Francisco de Assis [UNIFESP] (2009)
Objective: To establish the diagnosis of left ventricular hypertrophy (LVH) in haemodialysis (HD) patients with chronic kidney disease (CKD) using seven different electrocardiographic criteria and chest radiography, and to correlate these two diagnostic methods with left ventricular mass index (LVMI) as obtained by echocardiogram. Methods: Cross-sectional study including 100 patients (58 men and 42 women, mean age of 46.2 ± 14.0 years) with CKD of all causes, undergoing HD for at least six months. Echocardiogram, electrocardiogram and chest radiography were obtained from all patients, always up to one hour after the end of the HD sessions. Results: LVH was detected in 83 patients (83%), of which 56 (67.4%) presented a concentric pattern and 27 (32.6%) an eccentric pattern of LVH. The patients had been undergoing HD for a mean time of 50.7 ± 46.5 months, median of 33,5 months. The mean LVMI was 154.9 ± 57.3 g/m2. All electrocardiographic methods studied and the cardiothoracic ratio (CTR) had diagnostic sensitivity, specificity and accuracy higher than 50%. Using Pearson’s linear correlation with LVMI, only the Sokolow-Lyon voltage criterion did not present a 0.50 coefficient. The calculation of the likelihood ratio, in turn, showed that both ECG and chest radiography have a discriminatory power for the diagnosis of LVH in the population studied, with emphasis on for the Cornell product and Romhilt-Estes criteria. No correlation was found between LVMI and QTc and QTc dispersion. Conclusions: Electrocardiogram and chest radiography are safe, useful, efficient and highly reproducible methods for the diagnosis of LVH in HD patients. The usefulness of ECG is stressed by its ability to detect electrophysiological changes such as QTc and QTc dispersion.